Dual-step photo-induced self-assembled hydrogel for endogenous oral mucosal wound healing - Shaojun Fang; Qiangqiang Zhou; Mengqi Zhou; Changyi Li; Huaxing Xu; Hongyu Tang; Wanlu Zhang; Ruiqian Guo; Xiaoling Wei; Rongjun Zhang (Light: Science & Applications)
Abstract By introducing piezoelectric materials into hydrogel oral dressings, a microelectric field could be generated under stress stimulation, thus facilitating oral wound healing. However, to adapt to the moist and dynamic environment of the oral cavity, traditional “step-by-step” synthesis often requires the combination of materials with different functionalities. Given the property differences between these materials, this strategy typically involves complex experimental procedures and unnecessary energy consumption. In this study, with the concept of “integrated construction”, we innovatively proposed a dual-step photo-induced method and successfully fabricated composite hydrogels with excellent performance. We introduced abundant oxygen vacancies into ZnO, leveraging the enhanced interface dynamics to achieve sustained photo-induced effect. With a double-network polymer framework as a template, this method could achieve the photo-induced spontaneous in-situ synthesis of polydopamine (PDA) within hydrogel without any extra special experimental conditions and complex operation procedures. We conducted a thorough analysis of the mechanism underlying this photo-induced method and applied the as-prepared hydrogel for the treatment of oral wounds, which significantly accelerated the healing process due to the outstanding comprehensive performance of hydrogel. These results suggest novel ideas and theoretical support for the facile construction of high-performance hydrogels based on photodynamic principles, demonstrating immense potential for future applications in wound dressings.